The Development of Melodic Recitation Skills in Thai Poetry Using the Think-Pair-Share Technique Integrated with a Creative Learning Model for Grade 5 Students at Wat Khaenai School - คำพันธ์ ทรงสิทธิ์; บัวสำอางค์ พานิช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) develop the rhythmic reading skills of Thai poetry (Thai Melodious Recitation) among Grade 5 students using the Think-Pair-Share (TPS) technique integrated with Creative Learning; 2) compare students’ rhythmic reading abilities before and after the intervention; and 3) investigate student satisfaction toward this instructional approach. The study employed a quasi-experimental research design. The sample group consisted of 25 Grade 5B students, selected through cluster random sampling. The research instruments included: 1) lesson plans utilizing the Think-Pair-Share technique combined with Creative Learning; 2) a recitation performance record for the main poetic text "Knowledge is Like Merchandise" (Wicha Muean Sinkha) to track skill development during the lessons; 3) a rhythmic reading proficiency test; and 4) a student satisfaction questionnaire. Data were analyzed using mean (x), standard deviation (S.D.), and dependent samples t-test. • After the instruction, students achieved an average score of 85.90% in melodious intonation reading, which exceeded the set criterion of 80% in all aspects. • The melodious intonation reading skills of Prathomsuksa 5 students, after receiving instruction using the Think-Pair-Share technique combined with the constructivist learning model, were significantly higher than before the instruction at the .05 statistical level. • The overall satisfaction of the students towards the instruction using the Think-Pair-Share technique combined with the constructivist learning model yielded an average mean score of 4.99, which corresponds to the Highest Agreement level.